Reconstruction of Constitutional Responsibility in Financing Primary Education in Indonesia - Fajrianto, Fajrianto; Rizqi, Muhammad; Aryanda, Dhien Favian; Difari, Ahmad Dzaky (Jurnal Al Azhar Indonesia Seri Ilmu Sosial, 2025)
This study examines the reconstruction of the State’s constitutional responsibility in financing primary education in Indonesia following Constitutional Court Decision No. 3/PUU-XXII/2024. The ruling corrected the narrow interpretation of Article 34(2) of Law No. 20 of 2003 on the National Education System (Sisdiknas Law), which had limited free education to public schools and caused discrimination against students in private schools. Using a normative juridical method with statutory and conceptual approaches, the study analyzes two issues: the Court’s reasoning in expanding the meaning of “free primary education” to include private schools, and the constitutional implications of the decision for realizing the right to education. The findings show that the Court’s decision rests on five key grounds: the constitutional guarantee of primary education under Article 31(2) of the 1945 Constitution; misinterpretation of the Sisdiknas Law conflicting with justice; the strategic role of private schools; the principles of non-discrimination and equality before the law; and consistency with Article 13 of the ICESCR. The decision strengthens equitable access to education, expands State funding to private schools, and redefines the State’s role as the guarantor of every citizen’s constitutional right to education. Keyword: Financing; Primary Education; Constitutional Court